Serum high sensitivity C reactive protein levels in patients with diabetic retinopathy: a cross sectional study - Chaudhari, Harishchandra R.; Chaudhari, Gaurav A. (International Journal of Advances in Medicine, 2020)
Background: Diabetic retinopathy (DR) is one of the major visual morbidities associated with diabetes. This study determined the levels of serum high-sensitivity C-reactive protein (hs-CRP) in patients with DR and to correlate the estimated levels of serum hs-CRP with the severity of DR and other coexisting factors. Methods: This was a cross-sectional study conducted between March 2009 and August 2010 and included patients with type 2 diabetes mellitus (T2DM) with or without DR. A detailed fundus evaluation was performed using direct and indirect ophthalmoscopy. The retinopathies were observed and documented in accordance with the Kanski's system of classification as background DR (BDR), pre-proliferative DR (PPDR), and proliferative DR (PDR). Laboratory investigations determined the levels of fasting blood glucose (FBG), postprandial blood glucose (PPBG), glycosylated hemoglobin, urine albumin excretion, and serum hs-CRP levels. Results: In total, 80 patients with T2DM were included (DR group, n=40 [BDR, n=22; PDR, n=11; PPDR, n=7]; control group, n=40). Highest serum hs-CRP levels were found in PDR group (6.68 mg/L), followed by PPDR and BDR group (3.2 mg/L and 1.56 mg/L, respectively). The PDR group showed the longest duration of diabetes (16 years), highest FBG (221.8 mg/dL) and HbA1c (6.68 mg/L). The incidence of albuminuria and maculopathy was higher in PDR group (72.7% and 54.54%, respectively). A significant association of hs-CRP levels with DR in patients with T2DM was observed. A significantly (<0.005) positive correlation of hs-CRP was also observed with age, duration of disease, FBG, PPBG, and HbA1c. Conclusions: Patients with severe grades of retinopathy had significantly higher hs-CRP levels than patients with the milder grades.